Small women entrepreneurs in textile trade businesses in Dar es salaam,Tanzania - Chaula, Chaula (Mzumbe University, 2026)
A dissertation submitted in partial fulfillment of the requirements for the award of degree of Masters of Business Administration in Corporate Management (MBA-CM) to Mzumbe University, Dar es Salaam Campus College